Approaches to treatment of emerging Shiga toxin-producing Escherichia coli infections highlighting the O104:H4 serotype - Rahal, Elias A.; Fadlallah, Sukayna M.; Nassar, Farah J.; Kazzi, Natalie; Matar, Ghassan M. (Frontiers in Cellular and Infection Microbiology, 2015)
Shiga toxin-producing Escherichia coli (STEC) are a group of diarrheagenic bacteria associated with foodborne outbreaks. Infection with these agents may result in grave sequelae that include fatality. A large number of STEC serotypes has been identified to date including E. coli O104:H4, an emerging pathogen that resulted in a notorious outbreak that predominantly affected Europe in 2011 leading to about 4000 infections and 50 deaths. STEC pathogenicity is highly reliant on the production of one or more Shiga toxins that can inhibit protein synthesis in host cells resulting in a cytotoxicity that may affect various organ systems. Antimicrobials are usually refrained from in the treatment of STEC infections since they are believed to induce bacterial cell lysis and the release of stored toxins. Some antimicrobials have also been reported to enhance toxin synthesis and production from these organisms. Various groups have attempted the use of alternative treatment approaches including the administration of toxin-directed antibodies, toxin-adsorbing polymers, probiotic agents and natural remedies. The utility of antibiotics in treating STEC infections has also been reconsidered in recent years with certain modalities showing promise.